Jual Beli Tanah Berdasarkan Alas Hak Surat Keterangan Kepemilikan Tanah Di Tua Pejat Kepulauan Mentawai - Kristianus Zega (Nagari Law Review, 2018)
Title of land, deeds of sale and other means of evidence are evidences of land ownership. Another type of evidence is a land ownership certificate as the document asserting a basic right of land ownership. Such documents provides weak evidence, but in Indonesia, especially in Tua Pejat region of the Mentawai islands, this kind of evidence is still widely found and used by landowners. The article is discussing the legality of sale and purchase transaction on land which only proved with letter of Statement by Land Official. The method used in this research is empirical juridical (socio-legal research). The juridical approach involved analysis of various land regulations, while the empirical approach was used to examine and analyse the operation of the law in practice as could be observed from social behaviour along with its aspects and how the law works in the community. The research concludes that the Land ownership certificates in Tua Pejat region of the Mentawai islands are based on a Form Letter from the Head of the Regional Office of the National Land Agency of West Sumatera Number: 500/88/BPN-2007 dated February 8, 2007 regarding the purposes of right and land registration based on government regulation No. 24/1997 on land registration to adjust for areas whose land ownership is not based on Minangkabau customary law